2007
DOI: 10.1111/j.1600-0765.2007.00990.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of noncollagenous components by neutrophil elastase reduces the mechanical strength of rat periodontal ligament

Abstract: These results suggest that the increased neutrophil elastase observed in periodontal disease degrades the oxytalan fibers and interfibrillar substances in the periodontal ligament to decrease its mechanical strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
(66 reference statements)
0
15
0
2
Order By: Relevance
“…20,21,22 An increase in neutrophil elastase activity increases fibronectin degradation fragments and decreases periodontal mechanical strength. 23 In addition, clinical treatments such as scaling, root planning and curettage weaken elastase activity and restore cFn level. 24 …”
Section: Discussionmentioning
confidence: 99%
“…20,21,22 An increase in neutrophil elastase activity increases fibronectin degradation fragments and decreases periodontal mechanical strength. 23 In addition, clinical treatments such as scaling, root planning and curettage weaken elastase activity and restore cFn level. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Ujiie et al (2007) have also recently investigated the effect of treatment of PDL specimens with elastase on the mechanical strength [48]. They found that in vitro treatment with elastase increased fragmentation of the oxytalan fibres (Figure 7) and reduced the mechanical strength of the PDL specimen (Figure 8) in a concentration-dependent manner.…”
Section: The Mechanical Strength Of the Pdlmentioning
confidence: 99%
“…d: dentine; b: bone. * P < .05 compared with the control; † P < .05 compared with the elastase-treated specimens, reproduced from Ujiie et al (2008) [48], by permission.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, tension strain functionally regulates the microfibril assembly in periodontal ligament fibroblasts and thus may contribute to the homeostasis of oxytalan fibers in periodontal ligaments (Tsuruga et al, 2009). Likewise, increased neutrophil elastase observed in periodontal disease degrades the oxytalan fibers and interfibrillar substances in the periodontal ligament to decrease its mechanical strength (Ujiie et al, 2008).…”
Section: Discussionmentioning
confidence: 99%